Language Learning Styles and Strategies of Primary School Students - Armawati; Nursalim; Susilasari; Mastarina (Fakultas Keguruan dan Ilmu Pendidikan Universitas Dwijendra, 2025)
Language learning at the elementary school level has an important role in the cognitive and communication development of students. Each student has a different way of absorbing and understanding language which is influenced by their respective learning styles. Learning styles in language learning in 5th grade elementary school students. Learning style is an important factor that influences the effectiveness of understanding and retention of information. There are three main learning styles, namely visual, auditory, and kinesthetic. Therefore, this study aims to explore the dominant language learning styles and language learning strategies often used by elementary school students. This research used a mixed-methods approach, combining quantitative and qualitative data to provide a comprehensive analysis. Participants included 31 fifth-grade elementary school students and three Indonesian language teachers. Data collection was conducted using questionnaires, interview guides, and observation sheets. Quantitative data were analyzed descriptively, while qualitative data from interviews were examined thematically to support and enrich the quantitative findings. The results of this study showed that students who had a visual learning style were 11 students (35.48%), auditory 10 students (32.26%), and kinesthetic 10 students (32.26%). While for language learning strategies, teachers used 3 strategies, namely cognitive, metacognitive, and social-affective strategies. Solutions that can be done to improve the effectiveness of language learning, teachers need to apply methods that are appropriate to the various learning styles of students. A combination of visual media, discussions, and direct practice activities can help students understand the material better. In addition, assistance in using metacognitive strategies is also needed so that students can develop more optimal learning skills.